Diagnostic Difficulties of Mucopolysaccharidosis Type I Mild Forms: Clinical Cases - Nato D. Vashakmadze; Leyla S. Namazova-Baranova; Natalia V. Zhurkova; Ekaterina Yu. Zakharova; Elena J. Voskobaeva; Marina A. Babaikina; Lyudmila M. Mikhaylova ("Paediatrician" Publishers LLC, 2020)
Mucopolysaccharidosis type I mild forms include Scheie syndrome and Hurler-Scheie syndrome that are characterized by slow progression, intact intelligence, and primarily effect on visual organ, musculoskeletal and cardiovascular systems. Early diagnostics, multidisciplinary approach to examination and monitoring, timely management are crucial in maintenance of patients' quality of life, preventing complications development and early disability. The article provides the overview of published data and description of 3 clinical cases with mild course of mucopolysaccharidosis type I.